Effect of different concentrations of ionized water pH on qualitative characteristics of the egg of laying hens Lohmann strain - Hussein, Mohammed Ali; Ibrahim, Basil Mohammed (Journal of Kerbala for Agricultural Sciences, 2022)
This experiment was conducted to study the effect of ionized water on qualitative characteristics of the egg of layer hen from the period 25/October/2020 to 13/March/2021 (20 weeks). 105 hens (Lohmann-classic) strains were randomly divided into 5 groups (21 hen / group). Each group was subdivided into 3 replicates ( 7 hen / replicates). Hens in the control group provide tap water with pH (7.14), while hens in the 2nd and 3rd groups provide alkaline ionized water with pH (8.5, 9.5) respectively, 4th and 5th groups provide acidic ionized water with pH (5, 4) respectively. Results showed yolk weight rate significantly increase in the alkaline ionized water group (T2) as compared with the control and no significant differences were observed between groups on other egg quality traits. In addition, ionized water good method to improve water quality and some qualitative characteristics of eggs.